Isolation and characterization of bacteriocin‐producing bacteria from the intestinal microbiota of elderly Irish subjects - Lakshminarayanan, B.; Guinane, C.M.; O'Connor, P.M.; Coakley, M.; Hill, C.; Stanton, C.; O'Toole, P.W.; Ross, R.P. (Journal of applied microbiology, 2013)
Aims To isolate and characterize bacteriocins produced by predominant species of lactic acid bacteria from faeces of elderly subjects. Methods and Results Screening over 70 000 colonies, from faecal samples collected from 266 subjects, using the indicator organisms Lactobacillus bulgaricus LMG 6901 and Listeria innocua DPC 3572, identified 55 antimicrobial‐producing bacteria. Genomic fingerprinting following ApaI digestion revealed 15 distinct strains. The antimicrobial activities associated with 13 of the 15 strains were sensitive to protease treatment. The predominant antimicrobial‐producing species were identified as Lactobacillus salivarius, Lactobacillus gasseri, Lactobacillus acidophilus, Lactobacillus crispatus and Enterococcus spp. A number of previously characterized bacteriocins, including ABP‐118 and salivaricin B (from Lact. salivarius), enterocin B (Enterococcus faecium), lactacin B (Lact. acidophilus), gassericin T and a variant of gassericin A (Lact. gasseri), were identified. Interestingly, two antimicrobial‐producing species, not generally associated with intestinally derived microorganisms were also isolated: Lactococcus lactis producing nisin Z and Streptococcus mutans producing mutacin II. Conclusion These data suggest that bacteriocin production by intestinal isolates against our chosen targets under the screening conditions used was not frequent (0·08%). Significance and Impact of the Study The results presented are important due to growing evidence indicating bacteriocin production as a potential probiotic trait by virtue of strain dominance and/or pathogen inhibition in the mammalian intestine.